Sonographic assessment of fetal head deflexion using occiput: spine angle measured during first stage of labour and its role in predicting the mode of delivery among nulliparous women - Somu, Keerthi; S., Sujatha B.; Hebbar, Shripad; G., Shyamala; Pai, Muralidhar V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The attitude of the fetal head during labour significantly influences the progress and outcome of delivery and is mainly diagnosed by vaginal examination during labour. The aim of the study was to quantify the extent of deflexion of the fetal head by measuring the fetal occiput spine angle (OSA) through transabdominal ultrasonography in the first stage of labour and to determine whether the fetal OSA can predict the mode of delivery. Methods: We conducted a prospective observational study on 145 nulliparous uncomplicated singleton pregnant women without occiput-posterior position of the fetus during active labour. The OSA was measured as the angle between the two tangential lines to the occipital bone and the vertebral body of the first cervical spine, during active labour and monitored until delivery. Intra- and interobserver reproducibility of the OSA measurement and the correlation between the OSA and mode of delivery were also evaluated. Results: For the study population, the mean value of the OSA measured in the active phase of the first stage was 124.2±11.5⁰. The OSA measurement showed excellent intraobserver agreement (r = 0.82; 95% confidence interval [95% CI] 0.70-0.80) and fair-to-good interobserver agreement (r = 0.62; 95% CI 0.51-0.71). The mean OSA was significantly less for the group of patients who required conversion to cesarean section due to labour arrest (n=32) as compared to those who had vaginal delivery (n=113) (116.25±9.2⁰ versus 126.53±11.1⁰, P<0.01). An OSA of ≥121° was associated with vaginal delivery in 80.5% (91/113) of women, whereas 87.5% (28/32) of the women who delivered by cesarean section had an OSA <121⁰. Conclusions: Measurement of the OSA, by sonography is feasible, reproducible and an objective tool to assess the degree of fetal head deflexion during labour and to predict the mode of delivery.